Reaksi Pasar Modal Indonesia terhadap Peristiwa Politik Sebelum dan Setelah Pelantikan Presiden Prabowo-Gibran (Event Study pada Indeks Saham LQ45) - Fitroni Nuzula Putri; Mariana Mariana (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
This study aims to analyze the reaction of the Indonesian capital market to the inauguration of President Prabowo-Gibran using the event study method. The important variables in this study are abnormal returns and trading volume activity, with the population of all companies listed in the LQ45 stock index. The observation period was 14 days. The data consists of daily closing stock price, daily closing price of LQ45 IHSG, daily trading volume, and the number of shares outstanding. Hypothesis testing was conducted using the non-parametric Wilcoxon Signed Rank Test, as the data is not normally distributed. The results showed that there was no significant difference in the average abnormal return. However, a significant difference in the average trading volume activity was found between the periods before and after the presidential inauguration event.